(untitled) (Research, Society and Development, 2025)
This study aimed to evaluate whether pregnancy outcomes differ between single vitrified-warmed blastocyst transfers on days 5 and 6 in hormone replacement therapy cycles without preimplantation genetic testing (PGT). A retrospective cohort study was conducted between 2022 and 2023, involving 108 single blastocyst transfers, 64 on day 5 and 44 on day 6. Participants were women under 42 years old who underwent intracytoplasmic sperm injection (ICSI), excluding cycles involving egg donation, multiple transfers, natural endometrial preparation, or PGT. No significant differences were observed in pregnancy rates (44% vs. 45%, p = 1), clinical pregnancy rates (41% vs. 41%, p = 1), live birth rates (39% vs. 34%, p = 0.687), or miscarriage rates (11% vs. 25%, p = 0.267). The results suggest that day-6 blastocysts in cycles without PGT and with controlled endometrial preparation yield clinical outcomes similar to day-5 blastocysts, offering reassurance to clinicians and patients.